Isotopic study of rainfall and definition of local meteoric water lines: Case of the rainfall stations of the city of Bangui in Central African Republic - Foto, Eric; Allahdin, Oscar; Biteman, Olga; Poumaye, Nicole (European Journal of Chemistry, 2023)
The study of the isotopic composition of rainwater discussed in this article allows isotopic characterization of rainfall recorded in the Bangui region over 11 years at two stations. It will highlight the relationships between isotopes, climatic parameters, and temporal variation before defining the local meteoric line, which constitutes the reference point for the region. The results obtained after a follow-up of eleven years without interruption showed two major physical effects, the effect of the rainfall influences more strongly the composition in isotopes, the contents in isotopes vary inversely with the precipitation. For example, heavy rainfall in August and September saw a strong depletion of δ¹⁸O and δ²H contents. These values reach up to -4.96‰ for δ¹⁸O and -28.3‰ for δ²H. Similar, although weaker, effects are observed for July and October precipitation. We also note that the isotope contents at the Bangui University station are lower than those measured at the Bangui Sodeca station located at 386 m altitude on the Lower Ubangi Hill, which is similar to a pseudo-altitude effect. The evolution of stable isotope content in water as a function of meteorological parameters (temperature, rainfall, altitude) has allowed us to determine a local meteorological line for the city of Bangui from two measuring stations defined as follows: δ2H = 7.6 × δ18O + 10.4 (R2 = 0.9909) Université de Bangui, δ2H = 8.4 × δ18O + 12.5 (R2 = 0.9909) Bangui-Sodeca and δ2H = 7.9 × δ18O + 11.3 (R2 = 0.9939) Bangui local meteoric water lines.